Strategies for Obtaining Access to Secretive or Guarded Organizations. (December 2015) - Monahan, Torin; Fisher, Jill A.
Establishing contacts and gaining permission to conduct ethnographic or qualitative research can be time-consuming and stressful processes. Gaining access can be especially challenging when representatives of prospective research sites see their work as being sensitive and would prefer to avoid outside scrutiny altogether. One result of this dynamic is that many organizations that exert a profound influence in governing populations and regulating individuals' access to basic needs are relatively invisible to the public and shielded from meaningful public accountability. Therefore, it is vital to effectively study secretive or guarded organizations and fill out the empirical record, which in turn could create the conditions for greater public awareness and debate. To that end, this paper draws on our collective research experience and the scholarship of others to present nine strategies that we have found to be especially effective for securing access to secretive organizations.